Bali brand love: A perspective from domestic tourists - I Putu Gde Sukaatmadja; NI Nyoman Kerti Yasa; Putu Laksmita Dewi Rahmayanti (Cogent Business & Management, 2023)
This research aimed to examine and explain the effect of brand image, tourist experience, and destination quality on brand love, Word of Mouth (WOM), recommendation, and revisit intention. The research samples included 284 domestic tourists visiting Bali at least twice in the last 5 years. The research data were then analyzed using a path analysis with SEM-PLS. The research analysis results showed that all relationships had positive and significant effects, except tourist experience on WOM which had positive, but insignificant effect. It meant that tourist experience when traveling to Bali could not produce positive WOM. Brand image, experience, and destination quality are maintained to build high brand love for Bali. These also could generate positive WOM, higher recommendation level, and increase revisit intention of domestic tourists.
Keywords: M30; M31; M37; 650; and revisit intention; brand image; brand love; destination quality; experience; recommendation; WOM